2022
DOI: 10.1136/bmjpo-2021-001363
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of North West London healthcare utilisation by children during the COVID-19 pandemic

Abstract: ObjectiveTo explore the impact of the measures taken to combat COVID-19 on the patterns of acute illness in children presenting to primary and secondary care for North West London.Design/setting/participantsRetrospective analysis of 8 309 358 primary and secondary healthcare episodes of children <16 years registered with a North West London primary care practice between 2015 and 2021.Main outcome measuresNumbers of primary care consultations, emergency department (ED) attendances and emergency admissions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, although very few study sites restructured local healthcare pathways diverting urgent and emergency care to alternative healthcare facilities, this does not fully rule out changes to access to healthcare or parental health-seeking behavior. Mongru and colleagues showed that, for one of the sites included in this study, the distribution of patients across primary and secondary care was similar before and during the first year of the COVID-19 pandemic, suggesting the observed reductions in patient numbers, especially for those with minor injuries and illnesses, were a true reflection of fewer children in the community in need of urgent and emergency care [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although very few study sites restructured local healthcare pathways diverting urgent and emergency care to alternative healthcare facilities, this does not fully rule out changes to access to healthcare or parental health-seeking behavior. Mongru and colleagues showed that, for one of the sites included in this study, the distribution of patients across primary and secondary care was similar before and during the first year of the COVID-19 pandemic, suggesting the observed reductions in patient numbers, especially for those with minor injuries and illnesses, were a true reflection of fewer children in the community in need of urgent and emergency care [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, this decline could be attributed to the onset of the Covid-19 pandemic, which, at least during the first lockdown period, may have discouraged families from consulting larger hospitals. Many studies from different countries have shown a significant overall reduction in healthcare use by 2020 with respect to paediatric illnesses [ 13 ] and ENT consultations [ 14 , 15 ]. As the total number of patients had already decreased in 2019, the reason could also be explained by a decline in birth numbers registered from 2018 to 2019 by the Federal Statistical Office.…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions to the healthcare services of children with CAs were found to cause anxiety for parents,20 and fear that their child’s health may be negatively affected 22. Corcerns about SARS-CoV-2 infection were also common among parents,23 24 which coupled with reductions in other communicable infections during the pandemic,25 26 resulted in fewer visits to clinics25 27 and emergency departments26 28 in 2020. Parents reported a lack of support from healthcare professionals, including the absence of specific COVID-19-related guidance for children 22 29…”
Section: Introductionmentioning
confidence: 99%